Deep Breathing Relaxation Management to Reduce Pain in Bartholin's Cyst Patients: A Case Study - Hastuti, Ema Aprilia Setya; Sulastri, Sulastri (Jurnal Keperawatan Profesional (KEPO), 2025)
Bartholin's cyst is an enlargement of the Bartholin's gland that can interfere with a patient's quality of life due to symptoms of pain and discomfort. This case study aimed to determine the effectiveness of deep breathing relaxation therapy in reducing pain in a patient with a Bartholin's cyst. The patient was treated at the Ciputat Subdistrict Public Health Center, South Tangerang City, Banten Province, Indonesia. Initial assessment showed a nursing diagnosis of acute pain related to physiological injury agents (inflammation). After three consecutive days of deep breathing relaxation therapy, the patient's pain score decreased from 7 to 5 on a numeric pain rating scale. Deep breathing relaxation therapy can be effective in reducing pain in patients with Bartholin's cysts, as demonstrated in this case report.